Doradca zawodowy we współczesnym systemie edukacyjnym - Szczechowiak , Ewelina (Studia Edukacyjne, 2020)
Szczechowiak Ewelina, Doradca zawodowy we współczesnym systemie edukacyjnym [Career Advisors in the Contemporary Educational System]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 253-266. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.14 The position of a career advisor in the contemporary educational system is linked to challenges. The situation on the labor market and its changes over the years are crucial for vocational guidance and lifelong learning. Appropriate support from a specialist, parents of an apprentice and teachers can lead to future educational and professional success. Young people think about self-realization, development, and success; they notice that the course of a career in line with their assumptions depends on getting to know their strengths and weaknesses. The main task of career counselors is to help in choosing the further path of education, which is why their role is so important in the life of young people. The article deals with the reality and ideal model of a career advisor and shows the attitude of young people towards a specialist.